Post-adoption Behaviour of Farmers Towards Soil and Water Conservation Technologies of Watershed Management in Northern Shivalik Foothills - Arya, Swarn Lata; Tiwari, A K; Yadav, R P; Bagdi, G L (Indian Journal of Extension Education, 2020)
The study was undertaken at Indian Institute of Soil and Water Conservation Research Centre, Chandigarh from November, 2012 to June 2015 in five watersheds developed by the Centre, with the objectives to study the post-adoption behaviour of farmers regarding watershed technologies. The watersheds selected were i) AganpurBhagwasi watershed located in Patiala district, (Punjab State) ii) Johranpur watershed in Solan district, (H.P) iii) Mandhala watershed in Solan district, (H.P.) iv) Kajiana watershed in Panchkula district (Haryana) (v) Sabeelpur watershed in Panchkula district (Haryana). The post-adoption behaviour of 225 beneficiary farmers who haveadopted different soil and water conservation technologies for watershed management should be studied in detail regarding their present status of continue-adoption, diffusion, dis-adoption and also technological gap.Combining the data for all the five watersheds, it was concluded that 79 per cent of the farmers continued to adopt SWC technologies even after withdrawal of the project. Twenty one percent dis-continued the adoptionof technologies and 23 per cent were adopting with certain techological gap. The diffusion of adopted SWC technologies also occurred, and 16 per cent of SWC technologies were diffused to other farmers’ fields innearby areas for natural resource conservation on a watershed basis. The analysis revealed that the adoption and spreading of SWC practices is not only a technical problem that can be solved by research, but also a sociocultural and economic problem, with many constraints playing their role.